Impacto ambiental del espárrago (Asparagus officinalis) blanco en conserva, utilizando el Análisis del Ciclo de Vida - Polo Piminchumo, Karlita Melissa (2019)
The aim of this research was to determine the environmental impact of canned white asparagus (Asparagus officinalis) through the Life Cycle Analysis, which consists of 4 phases: Definition of the objective and scope, inventory analysis, environmental impact assessment and interpretation. For the environmental impact assessment, we used the Ecoindicator 99 methodology and the software Simapro 8.5. The main stage that generates the greatest environmental impact is the thermal treatment stage with 645.8501 Pt, which represents 42.79% and in second place is the blanching and cooling stage with 269.6428 Pt, which represents the 17.86% environmental impact of the canned white asparagus production. In both stages, the impact categories that are most affected are Inorganic Respiratory, climate change and the use of fossil fuels. Therefore, the category of Harm most affected is Human Health with 415.7208 Pt in the heat treatment stage and 173.6809 Pt in the blanching and cooling stage, which represents 27.54% and 11.51% respectively of environmental impact of the canned white asparagus production.